Organisational Structure and New Product Development in the Australian Grocery Market - Soldatos, Jerry; Hardy, Jurate (Ekonomika, 2004)
The paper examines the role that organisational structure plays in the new product development process. Various new product development organisational structures are examined and their influence on new product development activities is explained. A review of the literature on organisational structure alternatives for new product development is presented. The research found that the most common organisational structure used for new product development was the product manager and marketing manager.